Regulating Digital Finance for Small and Medium Enterprises Growth: Lessons From Thailand and Malaysia - Sugeng, Sugeng; Widya Romasindah Aidy (Universitas Airlangga, 2025)
This article aims to delve into how regulations and financial literacy policies can affect the growth of the Financial Technology (fintech) industry and contribute to increasing access to capital for Micro, Small, and Medium Enterprises (MSMEs). The focus of this research is to investigate the impact of regulations and financial literacy on access to capital for MSMEs through the use of financial technology. The research focuses on exploring the implementation of regulations and financial literacy policies in Thailand and Malaysia, as well as offering potential insights to deepen understanding of how regulations and financial literacy affect access to capital for MSMEs through the use of fintech in the context of Indonesia.The research method employs a doctrinal legal approach to analyze existing regulations and a literature review to understand the impact of financial literacy and financial technology. The research findings indicate that appropriate and responsive regulations, effective financial literacy programs, and good collaboration between the fintech industry and traditional financial institutions can enhance MSMEs' access to capital. The novelty of this research lies not only in its focus on Thailand and Malaysia but also in providing insights into the potential that can be developed within the context of Indonesia. However, in the context of Indonesia, challenges such as technological infrastructure and resistance to change still pose serious obstacles.